2019
DOI: 10.1002/vms3.167
|View full text |Cite
|
Sign up to set email alerts
|

Yupingfeng polysaccharides enhances growth performance in Qingyuan partridge chicken by up‐regulating the mRNA expression of SGLT1, GLUT2 and GLUT5

Abstract: The ban on the use of antibiotic in feed encouraged nutritionists to using alternatives to maintain growth performance and intestinal function of broilers. This study was conducted to evaluate the effects of Yupingfeng polysaccharides (YP) supplementation on growth performance and expression of SGLT1, GLUT2 and GLUT5 in Qingyuan partridge chicken. Experiment 1: a total of 540 chickens were randomly allocated to five groups with six replication. Dietary treatments were: (1) CON (control group), basal diet; (2) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
7
1

Year Published

2021
2021
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 42 publications
(31 reference statements)
1
7
1
Order By: Relevance
“…On the contrary, previous study has shown that UA inhibited the mRNA expression of SGLT1 and GLUT2 in intestinal epithelial cells (Wu et al, 2014). Yin et al (2019) demonstrated that up-regulated expression of SGLT1 could maintain growth performance and intestinal function of broilers (Yin et al, 2019). Besides, we found that UA promoted the expression of amino acid transporters (B 0 AT1, ASCT2, EAAT2, EAAT3).…”
Section: Discussioncontrasting
confidence: 68%
“…On the contrary, previous study has shown that UA inhibited the mRNA expression of SGLT1 and GLUT2 in intestinal epithelial cells (Wu et al, 2014). Yin et al (2019) demonstrated that up-regulated expression of SGLT1 could maintain growth performance and intestinal function of broilers (Yin et al, 2019). Besides, we found that UA promoted the expression of amino acid transporters (B 0 AT1, ASCT2, EAAT2, EAAT3).…”
Section: Discussioncontrasting
confidence: 68%
“…Our results indicated that dietary Bopu powder supplementation increased GLUT2 expression in the small intestinal mucosa of broiler chickens. Elevated GLUT2 mRNA levels typically contribute to intestinal digestive absorption (Yin et al, 2019). Dietary Bopu powder supplementation decreased caspase-3, caspase-8, and caspase-9 activities in the small intestine of broiler chickens, and addition of aureomycin to the diet reduced intestinal caspase-3 and caspase-8 activities.…”
Section: Discussionmentioning
confidence: 99%
“…Our results indicated that dietary Bopu powder supplementation increased GLUT2 expression in the small intestinal mucosa of broiler chickens. Elevated GLUT2 mRNA levels typically contribute to intestinal digestive absorption ( Yin et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…For example, 5- O -methylvisamminol (3’ hydroxylation), a metabolite of 5- O -methylvisamminol, played a vital role in the regulation of target of COVID-19, which could not be collected from databases directly. However, the research of the absorbed ingredients is based on the theory of that only some components absorbed in the body possess therapeutic effects, or produced from several reactions in the body ignoring components that play a regulatory role in intestinal flora to possess therapeutic effects, just like polysaccharides of YPF ( Yin et al, 2019 ). So, we will explore the effect of YPF on intestinal flora in the future research.…”
Section: Discussionmentioning
confidence: 99%